Spontaneous esophageal-pleural fistula - Vyas, Sameer (Medknow Publications, 2011)
Spontaneous esophageal-pleural fistula (EPF) is a rare entity. We describe a case in a middle-aged female who presented with severe retrosternal chest pain and shortness of breadth. Chest computed tomography showed right EPF and hydropneumothorax. She was managed conservatively keeping the chest tube drainage and performing feeding jejunostomy. A brief review of the imaging finding and management of EPF is discussed.